The Moderating Effect of Perceived Social Support on the Relation Between Heaviness of Smoking and Quit Attempts Among Adult Homeless Smokers - Neisler, Julie (Drug Alcohol Depend, 2018)
INTRODUCTION: Over 70% of homeless adults smoke cigarettes. Despite desire to quit, this group rarely receives the external support to make or maintain a successful quit attempt (SQA; intentional quit attempt lasting ≥24 hours). The Heaviness of Smoking Index (HSI) is a cigarette dependence measure that independently predicts SQAs among domiciled adults. For homeless adults, social support may be a way to buffer the impact of cigarette dependence on SQAs. METHODS: The association of the HSI and past-year SQAs, and the potential moderating role of social support, was examined among 445 homeless smokers (M(age)=43.2±11.8, 65% male, 57.5% white). Support was measured by the International Support Evaluation List (ISEL-12) and its 3 subscales: tangible, belonging, & appraisal support. RESULTS: The HSI was negatively correlated with SQAs (r=−.283, p<.01) and in a regression model controlling for age, sex, and race/ethnicity, appraisal support significantly moderated this relationship (p<.05). The HSI was significantly related to SQAs across low, moderate, and high levels of appraisal support [mean, ±1 SD; low (β=−.657, p<.001), medium (β=−.457, p<.001), and high (β=−.258, p<.05)]. Neither the ISEL-12 total nor the other subscales were moderators. CONCLUSION: The perceived availability of someone to talk to about one’s problems appeared to attenuate the strength of the inverse relationship between heaviness of smoking and SQAs. Fostering appraisal support for homeless smokers through group treatment may reduce the impact of cigarette dependence on making quit attempts. Social support coupled with the increased availability of empirically-supported cessation aids may improve dismal quit rates among homeless adults.